Factors Affecting Vegetable Marketing Channel In Rangamati Hill District of Bangladesh (Bangladesh Journal of Agricultural Research, 2022)
50 respondents were chosen randomly for primary data collection. In this study, principal component method was applied to estimate the factor loadings and communalities. ‘Varimax’ factor rotation was used to estimate factor loadings. The Kaiser-Meyer-Olkin (KMO) and Bartlett's Test were also applied. Besides, to identify the factors coefficient value and significance level multiple logistic regression model was applied. The study identified two major vegetable marketing channels, viz. Farmer- Local Market- Consumer and Farmer- Local Market- Local Retailer- Consumer; and three value addition activities, viz. washing, grading and bundling of vegetables. Problems associated with marketing channels were identified as lack of proper irrigation system, better transportation, diversified market, market infrastructure, storage facility, knowledge about new technology and marketing skill, proper guidance and training. The study recognized four factors that affect vegetable marketing channels. These are: Marketing factor (Factor 1), Economic factor (Factor 2), Social factor (Factor 3) and External factor (Factor 4). The study recommended that policy makers should come forward to ensure dissemination of appropriate technologies, adequate training for indigenous farmers, better transportation system, well established market infrastructure and integrate all activities of participants like farmers, local retailers, government, NGOs etc. to ensure a smooth, fair and profitable vegetable marketing channel.Bangladesh J. Agril. Res. 45(4): 445-454, December 2020